Analisis Rasio Terhadap Kinerja Keuangan Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2012 - Sejati, Nekat Dewi; , Dra. Mabruroh, M.M (2015)
The purpose of the research is to analyze the financial performance of banking companies are included in the indonesia stock exchange based on the result analysis of financial ratios on the financial statements of each company during the period 2010-2012. The used method is descriptive research by analyzing financial statements using quantitative data and data analysis techniques used is financial ratios, namely liquidity ratios, solvency ratio, profitability ratios, risk of effort bank ratios, and efficiency of effort ratio. Method intake of sample doing conducted at random, from thirtieth company of banking got ten company of banking. according to result of data analysis can know that measure with ratio of likuidity, profitability ratio, risk of effort bank ratios, and efficiency of effort ratios all company have good financial performance and measure with solvency ratio all company have unfavourable financial performance. Therefore all company of banking expected to look for capital addition, so ,can close possibility of loss in activity of credit with owned capital